2020
DOI: 10.1245/s10434-020-08632-1
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal Tumor Deposits in the Axillary Fat Indicate the Need for Axillary Dissection Among T1–T2cN0 Patients with Positive Sentinel Nodes

Abstract: Background:The ACOSOG Z0011 trial demonstrated the safety of omitting axillary dissection (ALND) in T1-T2cN0 patients with <3 positive sentinel nodes (SLN) undergoing breastconservation therapy. While microscopic extracapsular extension (mECE) >2mm is associated with increased nodal burden, the significance of extranodal tumor deposits (ETDs) in the axillary fat is uncertain.Methods: Consecutive patients with T1-T2cN0 breast cancer undergoing sentinel node biopsy and ALND for SLN metastases from 1/2010-12/2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…This varied practice highlights the need for a universal and standardized methodology to quantify ECE and prognostic significance of its extent. Another MSK series applying Z011 criteria, 33 showed that extranodal tumor deposit beyond the LN (which mimics our AXT definition here) is associated with more LN1 similar to the demographics presented in Table 1. However, they had only 113 AXT patients without any subclassification of AXT forms, and the authors clearly stated that they did not aim to correlate AXT with tumor outcomes and did not control for RLNR.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…This varied practice highlights the need for a universal and standardized methodology to quantify ECE and prognostic significance of its extent. Another MSK series applying Z011 criteria, 33 showed that extranodal tumor deposit beyond the LN (which mimics our AXT definition here) is associated with more LN1 similar to the demographics presented in Table 1. However, they had only 113 AXT patients without any subclassification of AXT forms, and the authors clearly stated that they did not aim to correlate AXT with tumor outcomes and did not control for RLNR.…”
Section: Discussionsupporting
confidence: 68%
“…However, they had only 113 AXT patients without any subclassification of AXT forms, and the authors clearly stated that they did not aim to correlate AXT with tumor outcomes and did not control for RLNR. 33 Our study shows the importance of expanding the focus beyond LN number/morphology and ECE. This is particularly important as the ongoing axillary de-escalation trials focus mainly on LN number/morphology with little to no mention of ECE and AXT.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation